Workplace Engagement of Librarians and Library Staff. Issue 1 (2nd January 2020) - Martin, Jason
Abstract: Very little has been written about engagement in the library workplace. Engagement and burnout are two poles on the workplace behavior spectrum. Burnout can be defined as exhaustion, cynicism, and reduced efficacy in daily work. Engagement can be defined as the opposite of burnout: energy, involvement, and high efficacy. Actively engaged employees are more satisfied in their jobs, and they are more likely to innovate and move into leadership positions. This study sought to understand the level of engagement of librarians and library staff. The Utrecht Work Engagement Scale (UWES) uses 17 questions to determine an individual's engagement in their work by measuring the three factors of vigor, dedication, and absorption. The scores (on a 0–6 scale) of participants ( n = 1100) for engagement was 4.25; vigor 4.15; dedication 4.52; and absorption 4.11. All of these scores are within the "average" range. Analysis found differences in levels of engagement by type of library (academic, public, special, and school) and work performed (administrative responsibility and patron interaction), but the differences were small. Open-ended responses revealed the main influences on participant engagement were workload, work fit, and work expectations; recognition; culture and environment; leadership; health; and meaning.